English Editions and Works by English-Speaking Authors in Sigismund Zois's Library. (18th September 2019) - Svoljšak, Sonja
Abstract: Baron Sigismund Zois of Ljubljana (1747–1819), who played a key role in the cultural and scientific advancement of the Enlightenment in Carniola, acquired an extensive book collection. Most of this collection, comprising 2, 295 titles in approximately 5, 000 volumes is now kept at the National and University Library in Ljubljana. This paper analyses a less known segment of Zois's library, the English editions and works by English-speaking authors that make up more than ten per cent of his collection, in relation to his scientific interests and to other specific circumstances. An attempt is made to reconstruct the acquisition channels for these English editions, based on Zois's remaining personal documents and correspondence. The collection was dispersed through the stacks during the 1820s and 1830s, and is currently being reconstructed as a part of the celebrations marking the 200th anniversary of Zois's death.